Physical character conductivity of system, including ethylene-propylene copolymer and SnCl2 - N. N. Komova; Yu. V. Sirov; M. D. Grigoriev (Тонкие химические технологии)
Shown that conductivity of ethylene-polypropylene copolymer filled SnCl2 has ionic character. The feasible mechanism of polymer electrolytes conductivity for system ethylene-polypropylene copolymer – inorganic salt is considered according to experimental data